Preparation method of gel composite material for improving water resistance and heat preservation of waste textiles
By performing hot water cleaning, refinement and modification on waste textiles, coating the fiber with low thermal conductivity material and performing spinning and drying processes, airgel material powder loss and waste textile recycling are solved. solve the difficult problem and achieve efficient preparation of waterproof and warm airgel composite materials.
Patent Information
- Application Number
- CN202411472294.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing aerogel materials are prone to powder loss in textile applications, affecting aesthetics and service life, and may have adverse effects on human health and the environment. At the same time, waste textiles face the challenges of cleaning, disinfection and fibrosis treatment during recycling and reuse, and it is difficult to effectively combine aerogel materials to prepare waterproof and warm composite materials.
Use hot water cleaning and alkaline solution to boil and remove oil and impurities, refine the fiber and perform the modification of the silicane coupling agent. Then apply low thermal guidance material coating on the fiber and enhance the cross-linking. The composite fiber is prepared through the wet spinning technology, and the solution-gel transformation and supercritical drying treatment will be performed. Essence
It has significantly improved the waterproofing performance of waste textiles, solves the problem of losing powder from gas gel materials, enhances the stability and durability of the material, and ensures the excellent heat insulation, waterproof and heating performance of composite materials.
Smart Images

Figure CN119332368A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of aerogels, and in particular to a method for preparing an aerogel composite material capable of improving the waterproofing and thermal insulation of waste textiles. Background Art
[0002] As the world's awareness of sustainable development and environmental protection increases, the recycling of waste textiles has become an important research field. Waste textiles are not only huge in quantity, but also cause serious environmental pollution if not properly handled. Therefore, exploring efficient and high-value recycling technologies for waste textiles has urgent practical significance and great application value.
[0003] As a material with excellent thermal insulation properties, aerogel has great potential for application in the field of thermal insulation. However, although aerogel materials are regarded as an ideal choice for thermal insulation materials due to their excellent thermal insulation properties, they face a significant problem in practical applications: powdering. This powdering phenomenon not only affects the aesthetics and service life of aerogel materials, but may also have adverse effects on human health and the environment. Especially in textile applications, the powdering problem will seriously affect the wearing experience and the overall quality of the product. Therefore, solving the powdering problem when aerogel is used as a thermal insulation material has become a hot topic and difficulty in current research.
[0004] At the same time, waste textiles often face challenges such as cleaning, disinfection, and fiberization during recycling and reuse. How to effectively remove grease and impurities from waste textiles and maintain the integrity of their fiber structure is the basis for achieving high-value reuse. In addition, effectively combining waste textiles with aerogel materials to prepare composite materials with excellent waterproof and thermal insulation properties is also an important direction of current research.
[0005] Therefore, it is necessary to provide a method for preparing aerogel composite materials for improving the waterproof and thermal insulation properties of waste textiles to solve the above technical problems. Summary of the invention
[0006] The invention overcomes the shortcomings of the prior art and provides a method for preparing an aerogel composite material for improving the waterproof and thermal insulation properties of waste textiles.
[0007] To achieve the above object, the technical solution adopted by the present invention is: a method for preparing a waterproof and thermal insulation aerogel composite material for waste textiles, comprising the following steps:
[0008] S1, washing with hot water and adding conventional detergent and non-ionic surfactant, and boiling with alkaline solution to remove grease and impurities and disinfect;
[0009] S2, refining the pretreated textile to form fibers;
[0010] S3, modifying the fiber with a silane coupling agent;
[0011] S4, coating the fiber with a low thermal conductivity material and performing cross-linking reinforcement;
[0012] S5. preparing composite fibers by wet spinning technology;
[0013] S6. Performing sol-gel transformation and drying treatment on the composite fiber obtained by wet spinning to finally obtain a waterproof and thermal insulation aerogel composite material.
[0014] In a preferred embodiment of the present invention, in S1, the temperature of hot water cleaning is 60-70°C, the alkaline solution is a NaOH solution with a concentration of 2-3%, and the boiling time is 1-2h.
[0015] In a preferred embodiment of the present invention, in S2, the length of the fibers after thinning is 1-3 mm.
[0016] In a preferred embodiment of the present invention, in S3, the silane coupling agent is γ-methacryloxypropyltrimethoxysilane, the mass ratio of which is 0.5-1% of the fiber mass, and the modification is carried out at pH 6-7 and temperature 40-50°C for 2h.
[0017] In a preferred embodiment of the present invention, in S4, the low thermal conductivity material coating is formed by mixing silica nanoparticles with a stabilizer, the stabilizer is polyvinyl alcohol or polyacrylic acid, and the composite coating is applied to the fiber by dipping and curing at 120°C for 30 minutes.
[0018] In a preferred embodiment of the present invention, trifluoroacetic acid is added as a crosslinking agent after the coating is cured, with a mass ratio of 1-3% of the fiber mass, and stirred at room temperature for 2 hours to enhance the network structure.
[0019] In a preferred embodiment of the present invention, in S5, polyvinyl alcohol is used as a binder in the wet spinning process, and its mass ratio is 10-15% of the fiber mass. Fibers with a specific structure are formed by high-speed stretching and shearing (skin speed ratio 1500rpm) and slow stretching (core speed ratio 300rpm), and heat-set at 120°C for 5 minutes.
[0020] In a preferred embodiment of the present invention, in S6, the sol-gel transition is carried out under acidic conditions of pH 3-4 for a duration of 3-4 hours.
[0021] In a preferred embodiment of the present invention, in S6, the drying process is supercritical drying, wherein the supercritical drying uses CO2 as a drying medium.
[0022] In a preferred embodiment of the present invention, in S6, the drying process is carried out at a temperature of 35-40°C and a pressure of 8-10 MPa, and the drying time is 10-20 hours.
[0023] The present invention solves the defects existing in the background technology and has the following beneficial effects:
[0024] (1) The present invention provides a method for preparing an aerogel composite material for improving the waterproof and thermal insulation of waste textiles. In step S4, a low thermal conductivity material coating formed by mixing silica nanoparticles and a stabilizer is applied, and trifluoroacetic acid is added as a cross-linking agent to enhance the network structure, thereby significantly improving the waterproof and thermal insulation performance of waste textiles, and effectively solving the problem of powdering when aerogel is used as a thermal insulation material. This step not only gives the composite material excellent thermal insulation performance and reduces heat loss, but also the coating formed by silica nanoparticles effectively blocks the penetration of moisture, so that the final aerogel composite material has excellent waterproof properties. At the same time, the addition of a cross-linking agent enhances the network structure of the coating, improves the stability and durability of the material, and effectively prevents the material from powdering during use.
[0025] (2) The present invention provides a method for preparing a composite aerogel material for improving the waterproof and thermal insulation of waste textiles. In step S5, wet spinning technology is used in combination with a specific adhesive and a stretching process to further enhance the structural stability of the composite fiber, which is crucial for improving the waterproof and thermal insulation effect of waste textiles and solving the problem of aerogel powder loss. By combining high-speed stretching and shearing with slow stretching, fibers with a specific structure are formed, which not only optimizes the arrangement and distribution of the fibers and improves the thermal insulation performance of the material, but also helps to maintain the morphological stability of the aerogel composite material and prevent the material from being damaged and powdered during use. At the same time, the use of adhesives also enhances the bonding force between the fibers, further improving the overall stability and durability of the material.
[0026] (3) The present invention provides a method for preparing an aerogel composite material that improves the waterproof and thermal insulation properties of waste textiles. The sol-gel transition and supercritical drying treatment in step S6 are key steps to solve the problem of aerogel shedding when used as a thermal insulation material, and also play an important role in improving the waterproof and thermal insulation effects of waste textiles. By precisely controlling the pH value and duration of the sol-gel transition and using supercritical drying technology with CO2 as the drying medium, the structural collapse and powdering that may occur in the traditional drying process are effectively avoided, ensuring that the final aerogel composite material has excellent physical stability and durability. This step not only solves the problem that aerogel materials are prone to shedding in practical applications, but also further improves their waterproof and thermal insulation properties by optimizing the microstructure of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art are briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative work.
[0028] Figure 1 It is a flow chart of a preferred embodiment of the present invention. DETAILED DESCRIPTION
[0029] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein. Therefore, the protection scope of the present invention is not limited to the specific embodiments disclosed below.
[0031] like Figure 1 As shown, the present invention provides a method for preparing an aerogel composite material for improving the waterproof and thermal insulation of waste textiles, comprising the following steps:
[0032] S1. Use hot water to wash and add conventional detergents and non-ionic surfactants, and use alkaline solution to boil to remove grease and impurities and disinfect. The temperature of hot water washing is 60-70°C, the alkaline solution is 2-3% concentration NaOH solution, and the boiling time is 1-2h;
[0033] S2, performing a thinning treatment on the pretreated textile, wherein the fiber length after the thinning treatment is 1-3 mm, and forming fibers;
[0034] S3, modifying the fiber with a silane coupling agent, wherein the silane coupling agent is γ-methacryloxypropyltrimethoxysilane, and the mass ratio thereof is 0.5-1% of the mass of the fiber, and the modification is carried out at a pH of 6-7 and a temperature of 40-50° C. for 2 hours;
[0035] S4, coating the fiber with a low thermal conductivity material coating and performing cross-linking reinforcement, wherein the low thermal conductivity material coating is formed by mixing silica nanoparticles with a stabilizer, wherein the stabilizer is polyvinyl alcohol or polyacrylic acid, and the composite coating is applied to the fiber by dipping and cured at 120° C. for 30 min, and after the coating is cured, trifluoroacetic acid is added as a cross-linking agent, and its mass ratio is 1-3% of the fiber mass, and stirred at room temperature for 2 h to enhance the network structure;
[0036] S5. The composite fiber is prepared by wet spinning technology. Polyvinyl alcohol is used as a binder in the wet spinning process, and its mass ratio is 10-15% of the fiber mass. The fiber with a specific structure is formed by high-speed stretching and shearing (skin speed ratio 1500rpm) and slow stretching (core speed ratio 300rpm), and heat setting is performed at 120°C for 5min.
[0037] S6. The composite fiber obtained by wet spinning is subjected to sol-gel transformation and drying treatment to finally obtain a waterproof and thermal insulation aerogel composite material. The sol-gel transformation is carried out under acidic conditions of pH 3-4 and lasts for 3-4 hours. The drying treatment is supercritical drying, in which supercritical drying uses CO2 as a drying medium. The drying treatment is carried out at a temperature of 35-40°C and a pressure of 8-10MPa, and the drying time is 10-20 hours.
[0038] It should be noted that:
[0039] In step S1, hot water is used for cleaning and conventional detergents and non-ionic surfactants are added, and a 2-3% concentration of NaOH alkaline solution is boiled at 60-70°C for 1-2 hours to effectively remove grease and impurities on the waste textiles and achieve thorough disinfection, laying a clean and sterile foundation for subsequent processing and ensuring the sanitary quality of the final product.
[0040] In step S2, the pretreated textiles are thinned to control the fiber length within the range of 1-3 mm. The thinning treatment not only increases the specific surface area of the fiber and enhances the bonding strength between the fiber and the subsequent coating, but also makes the fiber easier to disperse evenly in the subsequent process, thereby improving the overall performance of the composite material.
[0041] In step S3, γ-methacryloxypropyltrimethoxysilane is used as a silane coupling agent to modify the fiber at pH 6-7 and temperature 40-50°C, with the mass ratio controlled between 0.5-1% of the fiber mass and the reaction time being 2 hours. This step significantly improves the surface properties of the fiber, enhances the compatibility and bonding between the fiber and the coating material, and provides a strong guarantee for the preparation of high-performance composite materials.
[0042] In step S4, a low thermal conductivity material coating formed by mixing silica nanoparticles with polyvinyl alcohol or polyacrylic acid stabilizers is applied to the fiber, and the thermal insulation performance of the composite material is further improved through impregnation, curing and cross-linking enhancement treatment. The addition of trifluoroacetic acid as a cross-linking agent and stirring at room temperature for 2 hours effectively enhances the network structure of the coating, reduces the risk of coating shedding and powdering, and improves the durability and stability of the composite material.
[0043] In step S5, the composite fiber is prepared by wet spinning technology, using polyvinyl alcohol as a binder, and the composite fiber with a specific structure is formed by precisely controlling the process parameters of high-speed stretching and shearing (skin speed ratio 1500rpm) and slow stretching (core speed ratio 300rpm). The fiber is heat-set at 120°C for 5 minutes to ensure the shape stability and mechanical strength of the fiber.
[0044] Finally, in step S6, the composite fiber obtained by wet spinning is subjected to sol-gel transformation and supercritical drying. The sol-gel transformation is carried out under acidic conditions of pH 3-4 for 3-4 hours, successfully converting the composite fiber into an aerogel structure. The subsequent supercritical drying treatment uses CO2 as a drying medium and is carried out at a temperature of 35-40°C and a pressure of 8-10MPa for 10-20 hours, effectively avoiding cracks and shrinkage problems that may be caused by traditional drying methods, retaining the porosity and high specific surface area characteristics of the aerogel, thereby giving the composite material excellent waterproof and thermal insulation properties.
[0045] Embodiment 1:
[0046] S1: Preprocessing
[0047] Material preparation: Select 100g of waste textiles as raw materials, and prepare phosphorus-free laundry detergent, sodium dodecylbenzene sulfonate and 2% NaOH solution.
[0048] Operation steps: First, put the waste textiles into 65℃ hot water, add phosphate-free laundry detergent and sodium dodecylbenzene sulfonate, stir and wash for 30 minutes to remove the initial dirt. Then, transfer the textiles to a pot containing 2% NaOH solution, heat to boiling and continue boiling for 1.5 hours to thoroughly remove grease, impurities and disinfect. After the treatment is completed, rinse with clean water and dry naturally.
[0049] S2: Refinement
[0050] Operation steps: The pre-treated textiles are sent to the fiber refiner, where they are mechanically crushed and sieved to obtain refined fibers with a length of 1.5 mm. These fibers are collected and sorted for the next step of processing.
[0051] S3: Silane coupling agent modification
[0052] Material preparation: γ-methacryloxypropyltrimethoxysilane (as a silane coupling agent), deionized water, and acid or alkali solution for adjusting the pH value (such as dilute hydrochloric acid or sodium hydroxide solution).
[0053] Operation steps: put the refined fiber into the reactor, add an appropriate amount of deionized water, and adjust the pH value to 6.5. Then, add γ-methacryloxypropyltrimethoxysilane at a ratio of 0.75% of the fiber mass, and stir the reaction at 45°C for 2 hours. After the reaction, take out the fiber and wash it with deionized water, and place it in a drying oven for drying.
[0054] S4: Coating with low thermal conductivity material and cross-linking reinforcement
[0055] Material preparation: silica nanoparticles (particle size about 50 nm), polyvinyl alcohol (as a stabilizer), and trifluoroacetic acid (as a cross-linking agent).
[0056] Operation steps: First, silica nanoparticles are mixed with an appropriate amount of polyvinyl alcohol solution to prepare a low thermal conductivity material coating. Then, the modified fiber is immersed in the coating to ensure that the fiber surface is evenly coated. After that, the coated fiber is placed in a 120°C oven for curing for 30 minutes. After curing, trifluoroacetic acid is added as a crosslinking agent at a ratio of 2% of the fiber mass and stirred at room temperature for 2 hours to enhance the network structure of the coating.
[0057] S5: Preparation of composite fibers by wet spinning
[0058] Material preparation: polyvinyl alcohol (as adhesive), deionized water, spinning machine.
[0059] Operation steps: The coated and cross-linked reinforced fibers are mixed evenly with an appropriate amount of polyvinyl alcohol solution (12.5% of the fiber mass) to form a spinning solution. Subsequently, the spinning solution is injected into a wet spinning machine, and a composite fiber with a specific structure is formed through the process conditions of high-speed stretching and shearing (skin speed ratio 1500rpm) and slow stretching (core speed ratio 300rpm). After spinning, the composite fiber is heat-set at 120°C for 5 minutes to enhance its stability.
[0060] S6: Sol-Gel Transition and Supercritical Drying
[0061] Material preparation: acid solution (dilute hydrochloric acid adjusted to pH 3.5), supercritical drying equipment (including CO2 circulation system).
[0062] Operation steps: Place the heat-set composite fiber in an acidic solution and perform sol-gel transformation at pH 3.5 for 3.5 hours. After the transformation is completed, transfer the fiber to a supercritical drying device and use CO2 as the drying medium. Perform supercritical drying at a temperature of 37.5°C and a pressure of 9MPa for 15 hours. After drying, take out the fiber to obtain a waterproof and thermal aerogel composite material.
[0063] Comparative Example 1:
[0064] The third comparative example is substantially the same as the first comparative example, except that the step S1 is skipped directly, and the process starts from S2, and the waste textiles that have not been pretreated are used for subsequent treatment.
[0065] Comparative Example 2:
[0066] The third comparative example is substantially the same as the first comparative example, except that the step S2 is skipped and the pretreated textile (not refined) is directly used for the steps S3 and subsequent steps.
[0067] Comparative Example 3:
[0068] The third comparative example is substantially the same as the first comparative example, except that the step S3 is skipped and the refined fibers are directly used to perform the steps S4 and subsequent steps.
[0069] Experiment 1:
[0070] Weigh 100 g of samples of the same mass as those in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 respectively and conduct the following experiments to ensure that there are no loose particles on the surface;
[0071] Waterproof performance test: evaluate the waterproof performance through static water contact angle measurement and dynamic water absorption test;
[0072] Thermal insulation performance test: measure the thermal conductivity of aerogel (0.015W·(m·K)^-1 or less is excellent) and the thermal insulation effect in a simulated environment;
[0073] Mechanical strength test: compressive strength and elastic modulus tests were performed to evaluate the durability of the aerogel;
[0074] Temperature resistance test: Test the performance changes of aerogel under high temperature (200℃) and low temperature (-50℃) environments;
[0075] Powder loss performance test: Place the sample in a centrifuge tube and centrifuge it using a high-speed centrifuge (5000 rpm for 5 minutes). After centrifugation, collect the powder at the bottom and side walls of the centrifuge tube.
[0076] Table 1:
[0077]
[0078]
[0079] From Table 1 we can see that:
[0080] Waterproof performance:
[0081] Example 1: The performance is excellent, the static water contact angle is 152.45°, and the dynamic water absorption rate is only 0.23%, showing extremely strong waterproof ability.
[0082] Comparative Example 1: It decreased significantly, the static water contact angle dropped to 120.34°, and the dynamic water absorption rate increased to 1.56%, and the waterproof performance was poor.
[0083] Comparative Example 2: slightly inferior to Example 1, the static water contact angle and dynamic water absorption rate are 140.12° and 0.58% respectively, and the waterproof performance is acceptable.
[0084] Comparative Example 3: Insufficient, the static water contact angle and dynamic water absorption rate are 135.67° and 0.89% respectively, and the waterproof performance needs to be improved.
[0085] Thermal performance:
[0086] Example 1: Excellent, thermal conductivity as low as 0.012W·(m·K) -1 The thermal insulation effect reaches 10.56℃, showing excellent thermal insulation performance.
[0087] Comparative Example 1: Decreased, thermal conductivity increased to 0.018W·(m·K) -1 , the thermal insulation effect is reduced to 8.23℃, and the thermal insulation performance decreases.
[0088] Comparative Example 2: Slightly worse, thermal conductivity and insulation effect are 0.014W·(m·K) -1 and 9.34°C, the warmth retention performance is slightly inferior to that of Example 1.
[0089] Comparative Example 3: Decreased, thermal conductivity and insulation effect are 0.016W·(m·K) -1 and 9.01°C, the warmth retention performance is not as good as that of Example 1.
[0090] Mechanical strength:
[0091] Example 1: High, with a compressive strength of 2.89 MPa and an elastic modulus of 0.56 GPa, showing excellent mechanical strength.
[0092] Comparative Example 1: Significantly reduced, the compressive strength and elastic modulus were 1.67 MPa and 0.34 GPa respectively, and the mechanical strength was weak.
[0093] Comparative Example 2: Lower than Example 1, but higher than Comparative Example 1, the compressive strength and elastic modulus are 2.12 MPa and 0.45 GPa respectively, and the mechanical strength is medium.
[0094] Comparative Example 3: There is some improvement, but it still does not reach the level of Example 1. The compressive strength and elastic modulus are 2.45 MPa and 0.51 GPa respectively, and the mechanical strength is good.
[0095] Temperature resistance:
[0096] Example 1: Stable, the performance changes little under high and low temperature environments, respectively -2.34% and +1.23%, showing good thermal stability.
[0097] Comparative Example 1: Deterioration, the performance dropped significantly at high temperature (-10.56%), and also dropped to a certain extent at low temperature (-3.45%), and the temperature resistance was poor.
[0098] Comparative Example 2: The performance is between Example 1 and Comparative Example 1, with a small change in temperature resistance, but not as stable as Example 1.
[0099] Comparative Example 3: The temperature resistance is average, and the specific data is not directly given, but it is inferred based on other indicators that its temperature resistance may not be as good as that of Example 1.
[0100] Powder loss rate:
[0101] Example 1: Very low, the mass of the powder after centrifugation is 0.02g, indicating that the material surface has strong adhesion and is not easy to fall off.
[0102] Comparative Example 1: The powder mass after centrifugation was 0.15 g, the powder loss rate was high, and the surface adhesion of the material was weak.
[0103] Comparative Example 2: The powder loss rate is lower, but higher than that of Example 1. The mass of the powder after centrifugation is 0.08 g, and the adhesion needs to be improved.
[0104] Comparative Example 3: The powder loss rate is also high, and the powder mass after centrifugation is 0.12g, indicating that the coating adhesion needs to be strengthened.
[0105] In summary:
[0106] Example 1 shows significant advantages in many aspects such as waterproof performance, thermal insulation performance, mechanical strength, temperature resistance and powder loss rate. Its waterproof performance is particularly outstanding, with a static water contact angle of up to 152.45° and an extremely low dynamic water absorption rate of only 0.23%, showing extremely strong waterproof ability. At the same time, the thermal conductivity of Example 1 is as low as 0.012, the thermal insulation effect reaches 10.56°C, and the thermal insulation performance is excellent. In terms of mechanical strength, the measured compressive strength and elastic modulus are as high as 2.89MPa and 0.56GPa respectively, showing excellent mechanical stability. In addition, Example 1 also shows good thermal stability, and the performance changes in high and low temperature environments are minimal. The most impressive thing is its extremely low powder loss rate. The mass of the powder after centrifugation is only 0.02g, indicating that the material surface has strong adhesion and the coating is stable and reliable.
[0107] In summary, Example 1 is significantly superior to other comparative examples in all indicators, which fully demonstrates its excellent performance as a waterproof and thermal insulation aerogel composite material.
[0108] The above is based on the ideal embodiment of the present invention. Through the above description, relevant personnel can make various changes and modifications without departing from the technical concept of the present invention. The technical scope of the present invention is not limited to the content in the specification, and the technical scope must be determined according to the scope of the claims.
Claims
1. A method for preparing aerogel composite materials for improving the waterproof and thermal insulation of waste textiles, characterized in that: The following steps are involved: S1, washing with hot water and adding conventional detergent and non-ionic surfactant, and boiling with alkaline solution to remove grease and impurities and disinfect; S2, refining the pretreated textile to form fibers; S3, modifying the fiber with a silane coupling agent; S4, coating the fiber with a low thermal conductivity material and performing cross-linking reinforcement; S5. preparing composite fibers by wet spinning technology; S6. Performing sol-gel transformation and drying treatment on the composite fiber obtained by wet spinning to finally obtain a waterproof and thermal insulation aerogel composite material.
2. The method for preparing a waterproof and thermal insulation aerogel composite material for waste textiles according to claim 1, characterized in that: In S1, the temperature of hot water cleaning is 60-70°C, the alkaline solution is a NaOH solution with a concentration of 2-3%, and the boiling time is 1-2 hours.
3. The method for preparing a waterproof and thermal insulation aerogel composite material for waste textiles according to claim 1, characterized in that: In the S2, the length of the fibers after thinning is 1-3 mm.
4. The method for preparing a waterproof and thermal insulation aerogel composite material for waste textiles according to claim 1, characterized in that: In the S3, the silane coupling agent is γ-methacryloxypropyltrimethoxysilane, the mass ratio of which is 0.5-1% of the mass of the fiber, and the modification is carried out by reacting at pH 6-7 and temperature 40-50° C. for 2 hours.
5. The method for preparing a water-proof and heat-retaining aerogel composite material for waste textiles according to claim 1, characterized in that: In S4, the low thermal conductivity material coating is formed by mixing silica nanoparticles with a stabilizer, wherein the stabilizer is polyvinyl alcohol or polyacrylic acid, and the composite coating is impregnated on the fiber and cured at 120° C. for 30 minutes.
6. The method for preparing a water-proof and heat-retaining aerogel composite material for waste textiles according to claim 5, characterized in that: After the coating is cured, trifluoroacetic acid is added as a cross-linking agent with a mass ratio of 1-3% of the fiber mass and stirred at room temperature for 2 h to enhance the network structure.
7. The method for preparing a water-proof and heat-retaining aerogel composite material for waste textiles according to claim 1, characterized in that: In the S5, polyvinyl alcohol is used as a binder in the wet spinning process, and its mass ratio is 10-15% of the fiber mass. Fibers with a specific structure are formed by high-speed stretching and shearing (skin speed ratio 1500rpm) and slow stretching (core speed ratio 300rpm), and heat-set at 120°C for 5 minutes.
8. The method for preparing a waterproof and thermal insulation aerogel composite material for waste textiles according to claim 1, characterized in that: In the S6, the sol-gel transition is carried out under acidic conditions of pH 3-4 for a duration of 3-4 hours.
9. The method for preparing a waterproof and thermal insulation aerogel composite material for waste textiles according to claim 1, characterized in that: In S6, the drying process is supercritical drying, wherein the supercritical drying uses CO2 as a drying medium.
10. The method for preparing a water-proof and heat-retaining aerogel composite material for waste textiles according to claim 1, characterized in that: In S6, the drying process is carried out at a temperature of 35-40°C and a pressure of 8-10 MPa, and the drying time is 10-20 hours.
Citation Information
Cited By
Method for preparing composite material by recycling waste textile fabric
CN120243611A